Conditions for shale gas accumulation and the gas-bearing factors of the Wufeng-Longmaxi formation in the Laifeng–Xianfeng area - Shengling Jiang; Qinghua Zhou; Yanju Li; Rili Yang; Ruirui Zhao; Deqi Ma (Scientific Reports)
Abstract In this work, taking wells LD1, LD2, and LY2 in the Laifeng–Xianfeng area as the research target, through core description, intensive core sampling, experimental analysis, imaging logging and other methods, the characteristics of graptolite zone development, organic carbon content, mineral composition, shale reservoir properties and the gas-bearing properties of the Wufeng–Longmaxi Formation shale are systematically analyzed. The main factors affecting the gas-bearing capacity of the Wufeng–Longmaxi Formation shale are extensively evaluated. The results reveal the following: ① The Wufeng–Longmaxi Formation shale, which was deposited in a deep-water shelf environment, has a large thickness (50–60 m) and a stable distribution. The lower segment of the Wufeng–Longmaxi Formation shale is rich in graptolite fossils, and the thickness of the WF2–LM4 graptolite zone, which is the most favorable segment for shale gas development, is approximately 12 m (LD1), which is relatively thinner than the 25 m of well JY1. ② Wufeng-Longmaxi formation shale has characteristics of a high organic carbon content. However, the thickness of the organic-rich shale section is relatively thin (10–15 m), rich in brittle minerals, and has developed organic pores and microfractures as reservoirs; thus, the physical properties of the reservoir are characterized by a low porosity and ultralow–low permeability. On the basis of a comprehensive evaluation, the shale has the necessary conditions for gas enrichment. ③ The Langmuir volume of core samples from different wells located in different structural parts is relatively high, and is approximately 1.64–3.80m3/ t, while the gas content obtained from field desorption was quite different. The gas content of well LD1 (0.23–3.73 m3/t) and well LY2 (0.47–2.38 m3/t) located at the core of the Lianghekou syncline was greater than that of well LD2 (0.04–0.72 m3/t) located at the wing of the same syncline. The gas content of well LY2 located in the syncline core has characteristics that indicate significant changes in the longitudinal profile, and the gas content was much lower than that of well LD1, which is also located in the syncline core. ④ The high-quality material basis was the basic condition, and the good preservation conditions were the key factors for the high gas content of the Wufeng–Longmaxi Formation shale. The high-angle fractures and fracture zones formed by the NW high-angle strike-slip faults in the Laifeng–Xianfeng area are the main factors influencing the differences in the gas content of the shale in the different structural parts.